Sustainable Development Indicators: The Tyranny of Methodology Revisited - Bell, Dr Simon; Morse, Professor Stephen (Consilience, 2011)
Indicators are increasingly dominating our lives; whether we are aware of it or not. They have been popular tools for sustainable development policy makers, planners and managers, largely because they do the hard work of condensing complexity into single values that can be more easily digested and acted upon. But much power rests with those who select the indicators deemed to be important. This paper explores some of these issues at what is now regarded by some as the new frontier in “indicatorology‟; their use and influence. The authors argue that a new tyranny of methodology may be at play.